Penerapan Data Science untuk Mendukung Transformasi Digital UMKM di Kelurahan Kembangan Utara - Dwiasnati, Saruni; Devianto, Yudo; Gunawan, Wawan; Yuliarty, Poppy (Universitas Indraprasta PGRI, 2025)
The implementation of Data Science to support the digital transformation of SMEs (Small and Medium Enterprises) in Kelurahan Kembangan Utara aims to help local SMEs enhance their competitiveness through the utilization of digital technology. In the era of digitalization, SMEs need to adapt to changes in order to remain relevant and grow. Through the Data Science approach, this program focuses on utilizing data for market analysis, trend prediction, and business process optimization. Training provided to SME owners includes the application of data analysis algorithms, the creation of product recommendation systems, and the use of digital platforms that can improve operational efficiency and expand market reach. By integrating data-driven decision-making, SME owners can make more accurate decisions, increase sales, and open up new business opportunities. This program not only provides insights into the importance of digitalization but also equips participants with practical skills in using technologies relevant to the local market's needs. The expected outcome of this program is the improvement of the digital capacity of SMEs in Kelurahan Kembangan Utara, which in turn can contribute to the empowerment of the local economy.